Association between chronic hepatitis C infection and hepatocellular carcinoma in a Scottish population. Issue 1 (January 1997) - Haydon, G H; Jarvis, L M; Simmonds, P; Harrison, D J; Garden, O J; Hayes, P C
Abstract : BACKGROUND: Hepatocellular carcinoma (HCC) is one of the most common cancers in the world. The geographical prevalence varies considerably in different countries and Scotland is regarded as an area of low risk for the disease. AIMS: To assess the association between chronic hepatitis C infection (HCV) and HCC in a population of patients presenting to a single hospital. PATIENTS: One hundred and fourteen cases of histologically confirmed liver cancer presenting to the Royal Infirmary of Edinburgh between 1985 and 1994 were examined. METHODS: Of 114 cases of HCC, 80 samples of stored sera were available. Samples positive for HCV Ab were genotyped by restriction fragment length polymorphism analysis of HCV c-DNA. A population of 29 cirrhotic patients (diagnosed between 1985 and 1994) with chronic HCV infection was also genotyped. RESULTS: Chronic HCV infection was a major risk factor (30% of tested HCC patients) identified. HCV genotype 1b was predominant (16 of 20 patients). The time from HCV transmission to development of cancer ranged from 10 to 50 years (median 30). In the cirrhotic patient population, a broader distribution of genotypes was present (genotype 1a: 7; genotype 1b: 8; genotype 2b: 3; genotype 3a: 8 and genotype 4: 2). However, this population was significantly younger. (Mean (SD) 52 (14.5) years) (p = 0.0002) and demonstrated a significantly shorter duration of infection: range 10-40 years (median: 19). CONCLUSION: There is a strong association between chronic HCV infection, cirrhosis, and hepatocarcinogenesis in this Scottish population. The study was unable to distinguish whether the high prevalence of genotype 1b in the HCC population reflected increased oncogenicity in itself, or whether 1b was simply the most prevalent genotype in Scotland when these patients were infected.